Pengembangan Kurikulum Pendidikan Agama di Pesantren, Sekolah dan Madrasah - Murniati, Murniati; Salsaria, Rima; Kesuma, Adinda Retno (Pascasarjana IAIN Lhokseumawe, 2023)
The Islamic Religious Education (PAI) curriculum plays a strategic role in shaping the character, spirituality, and competencies of students across various Islamic educational institutions, including pesantren, madrasah, and public schools. Differences in curricular approaches and structures among these institutions highlight the need for a conceptual study to formulate a more integrative and contextually relevant curriculum development framework. This study employs a qualitative approach using library research methods. Data were collected through a comprehensive review of scholarly literature, policy documents, and relevant previous studies. The analysis was conducted using descriptive-analytical techniques and thematic interpretation to identify patterns, relationships, and conceptual syntheses that support the development of an integrated PAI curriculum. The findings reveal that pesantren curricula emphasize theocentric principles and experiential learning, while madrasah curricula integrate religious and general education within the framework of national policy. In contrast, public schools implement PAI as part of the formal education system through dichotomous, mechanistic, and organismic models. These three approaches hold potential to be further developed into a more holistic and transformative curriculum. This study proposes a conceptual framework for an integrated PAI curriculum that combines Islamic values with scientific knowledge and 21st-century skills.